Modifiable clinical and lifestyle factors are associated with elevated alanine aminotransferase levels in newly diagnosed type 2 diabetes patients: results from the nationwide DD2 study. Issue 8 (November 2014) - Mor, Anil; Svensson, Elisabeth; Rungby, Jørgen; Ulrichsen, Sinna Pilgaard; Berencsi, Klara; Nielsen, Jens Steen; Stidsen, Jacob Volmer; Friborg, Søren; Brandslund, Ivan; Christiansen, Jens Sandahl; Beck‐Nielsen, Henning; Sørensen, Henrik Toft; et al.
Abstract Background Current literature lacks data on markers of non‐alcoholic fatty liver disease (NAFLD) in newly diagnosed type 2 diabetes mellitus (T2DM) patients. We therefore, conducted a cross‐sectional study to examine modifiable clinical and lifestyle factors associated with elevated alanine aminotransferase (ALT) levels as a marker of NAFLD in new T2DM patients. Methods Alanine aminotransferase levels were measured in 1026 incident T2DM patients enrolled in the nationwide Danish Centre for Strategic Research in Type 2 Diabetes (DD2) cohort. We examined prevalence of elevated ALT (>38 IU/L for women and >50 IU/L for men) and calculated prevalence ratios associated with clinical and lifestyle factors using Poisson regression. We examined the association with other biomarkers by linear regression. Results The median value of ALT was 24 IU/L (interquartile range: 18–32 IU/L) in women and 30 IU/L (interquartile range: 22–41 IU/L) in men. Elevated ALT was found in 16% of incident T2DM patients. The risk of elevated ALT was increased in patients who were <40 years old at diabetes debut [adjusted prevalence ratio (aPR): 1.96, 95% confidence interval (CI): 1.15–3.33], in those with alcohol overuse (>14/>21 drinks per week for women/men) (aPR: 1.60, 95% CI: 1.03‐2.50), and in those with no regular physical activity (aPR: 1.42, 95% CI: 1.04–1.93). Obesity and metabolic syndrome per se showed no association with elevated ALT when adjusted for other markers, whereas we found positive associations of ALT with increased C‐peptide (β = 0.14, 95% CI: 0.06–0.21) and fasting blood glucose (β = 0.07, 95% CI: 0.03–0.11). Conclusions Among newly diagnosed T2DM patients, several modifiable clinical and lifestyle factors are independent markers of elevated ALT levels. Copyright © 2014 John Wiley & Sons, Ltd.